Behavioral decoding of Drosophila locomotion in a circular arena - Qiu,Shuang; Robertson,R Meldrum; Xiao,Chengfeng (PeerJ Preprints, 2017)
Motion detection and position tracking of animal behavior over a period of time produce massive amount of information, but analysis and interpretation of such huge datasets are challenging. Here we describe statistical methods to extract major movement structures of Drosophila locomotion in a circular arena, and examine the effects of pulsed light stimulation on these identified locomotor structures. Drosophila adults performed exploratory behavior when restrained individually in the circular arenas (1.27 cm diameter 0.3 cm depth). Measures of the distance to the center of the arena followed a gumbel distribution with mixed components. Representation learning of distance to center from 177,000 observations (from 63 controls and 55 flies with pulsed light stimulation) revealed three major movement components, indicating three locomotor structures characterized as: side-wall walk, angle walk and cross of the central region. Pulsed flies showed reduced cross of the central region compared with controls. We also showed that counter-clockwise walk and clockwise walk were the two major rotation behaviors with equal time proportion. There was a peak relative turning angle at 25.6o for counter-clockwise walk, and 334.4o for clockwise walk. Regression analysis of relative turning angle as a function of distance to center indicated that as distance to center increased, flies switched turning from directions for perimeter-returning to directions for major rotation. Pulsed flies reduced trajectories that had irregular circle-shape and increased trajectories with regular circle-shape during rotation. Taken together, we present a feasible approach to extract major locomotor structures of Drosophila locomotion in a circular arena, and demonstrate how pulsed light stimulation increased the regularity of locomotor trajectory.
Keywords: modeling; locomotor structure; Drosophila melanogaster; animal behavior; rotation behavior; locomotor regularity; gumbel distribution